Restoring the original taxonomic concept for Navarretia minima (Polemoniaceae): a revised synonymy and new combination - Johnson, Leigh A.; Gowen, David (Phytotaxa, 2022)
The taxonomic concept for Navarretia minima, when treated as a species or as a subspecies of N. leucocephala, has drifted dramatically from the protologue and original material on which the name is based. Taxonomic concepts from regional floristic works are reviewed to understand the historical context of this drift. Navarretia minima is re-established in a manner consistent with the protologue and original material. Navarretia furnissii is placed in synonymy under N. minima, and a new combination, N. leucocephala subsp. suksdorfii comb. et stat. nov., is established as the proper name for plants that morphologically fit the contemporary, prevailing concept for N. leucocephala subsp. minima. This new combination is based on N. suksdorfii, a taxon that has either been ignored or considered in synonymy under N. minima. Lectotypification is provided for both N. minima and N. suksdorfii.